Efek Daun Dewa (Gynura pseudo-china Aug D.C.) terhadap Peningkatan Trombosit Tikus Putih yang Diinduksi Hidroksi Urea - Winarno, M. Wien; Suciati, Yesi; Sediarso, H. (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2009)
Daun dewa (Gynura pseudo-china Aug. DC), empirically used as anti-inﬂammation, anti-diare, anti-tumor, and anti-fungus Additionally, it also used to prevent blood vessel contriction, and stimulate the immune system. The leaf ﬂom Daun Dewa empirically used to dengue fever treatment. In this study, 25 white rats Wistar strain were used which is divided into 5 groups J I) control group, 2) study group, which is divedid into 3 doses (100 mg, 200 mg, 400 mg/200g body weight) and 3) the normal control group (without induced). Hydroxy urea dose 27 mg/200 g body weight 2 times a day for induced. The treatment given 8 days dividing and every 2 days once done taking 0,5 ml of blood via the tail vein. Result showed ethanol leaf extract of Daun dewa dose 100 mg, 200 mg, and 400 mg/ 200 g body weight increase thrombocyte. Incease thrombocyte going on forth day aﬁer the test dose, and the sixth day amount thrombocyte have reached normal.